2016
DOI: 10.1002/etc.3491
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of bisphenol A diglycidyl ether (epoxide resin badge) during the early life cycle of a native amphibian species

Abstract: Bisphenol A diglycidyl ether (BADGE) is used in packaging materials, in epoxy adhesives, and as an additive for plastics, but it is also a potential industrial wastewater contaminant. The aim of the present study was to evaluate the adverse effects of BADGE on Rhinella arenarum by means of standardized bioassays at embryo-larval development. The results showed that BADGE was more toxic to embryos than to larvae at all exposure times. At acute exposure, lethality rates of embryos exposed to concentrations of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“… Masuo et al [ 11 ]: locus ceruleus is enlarged in treated male rats and neurodegenerative disorders. 18 Bisphenol A diglycid ether Plastics monomer Hutler et al [ 84 ]: the main abnormalities in amphibians larvae related to neurotoxicity. 19 Bisphenol F Plastics monomer Ohtani et al [ 85 ]: exposure alters offspring behavior, resulting in increases in anxiety and depressive state in mice.…”
Section: Resultsmentioning
confidence: 99%
“… Masuo et al [ 11 ]: locus ceruleus is enlarged in treated male rats and neurodegenerative disorders. 18 Bisphenol A diglycid ether Plastics monomer Hutler et al [ 84 ]: the main abnormalities in amphibians larvae related to neurotoxicity. 19 Bisphenol F Plastics monomer Ohtani et al [ 85 ]: exposure alters offspring behavior, resulting in increases in anxiety and depressive state in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a synthetic ligand of PPARγ, BADGE (Wright et al, 2000), showed significant effect on PSO development at 1 -5 µM. Similar cocnentrations of BADGE also caused neurodevelopmental toxicity in an amphibian (Rhinella arenarum, EC50 = 0.5 µM) (Hutler et al, 2016).…”
Section: Phenotypes Of Edcs and Nrs Ligandsmentioning
confidence: 95%
“…The incompletely polymerized BADGE will migrate into food and become a contaminant due to its toxicity to human. The harmful of BADGE of the human body is quite extensive, including endocrine disruption, cytotoxicity of human placenta, embryotoxicity and carcinogenicity . In addition, various derivatives such as bisphenol A (3‐chloro‐2‐hydroxypropyl) glycidyl ether (BADGE⋅HCl), bisphenol A bis(3‐chloro‐2‐hydroxypropyl) ether (BADGE ⋅ 2HCl) and bisphenol A (3‐chloro‐2‐hydroxypropyl) (2,3‐dihydroxypropyl) ether (BADGE⋅H 2 O⋅HCl) are also produced when BADGE is contacted with aqueous and/or acidic substrates, which also have been shown to pose a great threat to living things .…”
Section: Introductionmentioning
confidence: 99%